Association between the CALLY index, vitamin D, and asthma: insights from NHANES - Liu, Yachun; Wei, Yufeng (Frontiers in Allergy, 2025)
PurposeThe CALLY index integrates C-reactive protein (CRP), albumin and lymphocyte counts to accurately reflect the inflammatory, nutritional and immune status of the body. Multiple studies have indicated that the CALLY index plays a key role in a variety of diseases, especially asthma, and is closely associated with inflammatory response, airway remodeling and immune imbalance in asthma. Research has shown that vitamin D is associated with asthma susceptibility, severity, and control, and its levels may influence inflammatory and immune markers associated with the CALLY index, which may play a role in the association between the CALLY index and asthma.PatientsUsing data from the National Health and Nutrition Examination Survey (NHANES) from 2001 to 2010, the association between CALLY index and asthma and the role of vitamin D in American adults were analyzed in depth. Through multiple logistic regression, subgroup analysis, and other statistical means, the potential pathophysiological links between the three are revealed, providing theoretical support for the prevention and treatment of related diseases.ResultsA total of 17,946 individuals were included in this study, of which 2,317 were diagnosed with asthma. Fully adjusted multivariate logistic regression analysis revealed that the CALLY index was significantly negatively associated with asthma, with an odds ratio (OR) of 0.996 [95% confidence interval (CI) 0.993–0.999]. Specifically, each unit increase in the CALLY index was associated with a 0.996-fold reduction in asthma risk. In addition, mediation effect analysis showed that vitamin D partially mediated the association between the CALLY index and asthma, with a mediation ratio of 3.36%.ConclusionThis study reveals an association between the CALLY index and reduced risk of asthma in the US population and suggests that vitamin D plays an incomplete mediating role. This finding provides a new theoretical basis for the diagnosis, treatment, and prevention of asthma and is expected to be a potential biomarker.